Purpura fulminans related to a probable case of staphylococcal toxic shock syndrome in the Hospital III Cayetano Heredia, Piura, Perú - La Rosa Zambrano, Daniel G. (2008)
Introduction: Purpura fulminans due to staphylococcal infection, is an uncommon association which had been observed frequently in the last years.Case report: Purpura fulminans related to a probable case of staphylococcal toxic shock syndrome in a 20 years old female patient is presented. She was admitted in the emergency room and septic shock of gynecologic origin and multiple organ failure were diagnosed, and she required surgical intervention. While she was in the intensive care unit she improved hemodynamic condition, but she developed purpura and digital necrosis in both feet and in the second finger of the right hand. She was transferred to the internal medicine service and finally, she was discharged from hospital.